15. SPECIES COMPOSITION, DISTRIBUTION OF ANOPHELES MOSQUITOES, AND FEEDING BEHAVIOR OF MALARIA VECTORS IN PA VE SU AND TA BA COMMUNES, MUONG TE DISTRICT, LAI CHAU PROVINCE, 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To identify the species composition of Anopheles spp. mosquitoes and the feeding behavior of malaria vectors in Pa Ve Su and Ta Ba communes, Muong Te district, Lai Chau province. Methods: The study was conducted from July to December 2024 in the two communes of Pa Ve Su and Ta Ba, Muong Te district, Lai Chau province. All Anopheles spp. mosquitoes in two habitats were collected using survey methods following the procedures of the National Institute of Malariology, Parasitology, and Entomology. Results: A total of 11 Anopheles spp. species were collected from the survey sites: 11 species in Pa Ve Su and 10 species in Ta Ba. Two secondary vectors, An. maculatus and An. sinensis, were identified at the survey sites, while the primary vector An. minimus was not found. In Pa Ve Su, species diversity was higher in residential areas (10 species) compared to farming areas (5 species). The proportions of An. maculatus and An. sinensis in residential areas and farming areas were 39.33%, 42.51% and 51.76%, 45.42%, respectively. Their outdoor biting activities were higher than indoor biting, with rates of 83.58% and 81.26% compared to 16.42% and 18.74% (p < 0.05). In Ta Ba, species diversity was also higher in residential areas (9 species) than in farming areas (7 species). The proportions of An. maculatus and An. sinensis in residential areas and farming areas were 43.25%, 46.18% and 42.06%, 54.41%, respectively. Similarly, outdoor biting activities were higher than indoor biting, with rates of 82.34% and 82.78% compared to 17.66% and 17.22% (p < 0.05). Feeding activity occurred between 6:00 PM and 12:00 AM, with the peak outdoor biting period between 8:00 PM and 10:00 PM. Conclusion: The species composition of mosquitoes in Pa Ve Su and Ta Ba communes was more diverse in residential areas than in farming areas. An. maculatus and An. sinensis were predominant in both residential and farming areas. These vectors exhibited feeding activity throughout the period from 6:00 PM to 12:00 AM, with outdoor biting being more intense than indoor biting, particularly between 8:00 PM and 10:00 PM.
Keywords: Anophele; distribution; feeding behavior